Development of Ethnomathematics-Based Module to Improve Students’ Critical Thinking Skills - Elfi Indriani; Ahmad Fauzan; Azmi Syarif; Melva Zainil; Nurhizrah Gistituati (STAI Hubbulwathan Duri, 2024)
Critical thinking skills are crucial for students as they are closely tied to their problem-solving capabilities. This study aims to develop a teaching module integrated with the ethnomathematics of the Jam Gadang architecture to enhance students' critical thinking skills on the topic of flat shapes. This research adopts a Research and Development (RD) approach using the Plomp model. The study involves fifth-grade students from a state elementary school in Sungai Jariang in a one-to-one and small-group method trial class, and a state elementary school in Pahambatan Balingka as a field trial class. Data analysis employs validity analysis techniques, practicality analysis techniques utilizing a Likert scale, and effectiveness analysis techniques using a one-group pretest-posttest design. The research instruments include a questionnaire and a critical thinking test. Validation of the teaching module instrument scored 3.6, and student worksheets (LKPD) scored 3.83, both falling into the highly valid category. The practicality of the teaching module reached 92.86%, while the practicality of student worksheets (LKPD) reported 91.18% from the students' perspective and 95.85% from the teacher's perspective, all categorized as highly practical. The Jam Gadang integrated learning modules for ethnomathematics were declared effective in the medium category based on the calculated N-Gain value in field trials of 0.51. Thus, this learning module is suitable for use in improving students' critical thinking skills.